Survival benefit of prophylactic cranial irradiation in limited-stage small-cell lung cancer in modern magnetic resonance imaging staging: a systematic review and meta-analysis. (4th March 2023) - Liu, Jianjiang; Shen, Bin; Yang, Yang; Guo, Jiayi; Ren, Wei; Zhou, Qingbo; Mao, Jiwei; Ye, Wanli; Wu, Dongping
Abstract: Background: The use of prophylactic cranial irradiation (PCI) in patients suffering from limited-stage small-cell lung cancer (LS-SCLC) remains controversial in modern brain magnetic resonance imaging (MRI) staging. To this end, a systematic review with meta-analysis was hereby performed to investigate the overall survival (OS) in these patients. Methods: Relevant studies from the PubMed and EMBASE databases were reviewed, and pooled hazard risks were obtained using fixed-effects models. The PRISMA 2020 checklist was used. Results: Fifteen retrospective studies were identified, with a total of 2, 797 patients with LS-SCLC included in the analysis, 1, 391 of which had received PCI. For all included patients, PCI was associated with improved OS [hazard ratio (HR): 0.64, 95% confidence interval (CI): 0.58–0.70]. The combination of subgroup analysis and sensitivity analysis suggested that the effect of PCI on OS was independent of primary tumor treatment, proportion of complete response (CR), median age, PCI dose, publication years, etc. Additionally, the OS curve of 1, 588 patients having undergone thoracic radiotherapy (TRT) as the primary tumor treatment from 8 studies were reconstructed, and the pooled 2-, 3- and 5-year OS rates of limited stage patients were 59% vs. 42%, 42% vs. 29% and 26% vs. 19% (HR: 0.69, 95% CI: 0.61–0.77) in the PCI group and the no PCI group, respectively. Another reconstructed OS curve of 339 patients having undergone radical surgery as the primary tumor treatment from 2 studies presented better results, and the pooled 2-, 3- and 5-year OS rates of in the PCI group and the no PCI group were 85% vs. 71%, 70% vs. 56% and 52% vs. 39% (HR: 0.59, 95% CI: 0.40–0.87), respectively. Conclusions: This meta-analysis demonstrates a significant beneficial effect of PCI on the OS in patients with LS-SCLC in modern pretreatment MRI staging. However, considering the absence of a strict follow-up of brain MRI recommended by the guideline for the control group from most of the included studies, the superiority of PCI to the treatment strategy of no PCI plus brain MRI surveillance remains unclear.